Change in the dynamics of salinity and water quality of an island estuary by the discharge of effluents - Rodrigues,Claudinei José (2021)
ABSTRACT Anthropic changes in coastal watersheds affect the quantity and quality of water in estuaries. Based on an analytical model of saline intrusion and load balance, we have evaluated the effects of effluent discharge (mean of 285 L·s−1 and peak of 495 L·s−1) from a wastewater treatment plant (WWTP) in an island estuary. Saline intrusion at low tide, without actual anthropic discharge, will increase by 22%, whereas with increasing discharge, reductions of 16% and 28%. The reduction of saline intrusion may affect biogeochemical processes and the distribution of species in regions further up the estuary. When the WWTP reaches the mean projected discharge, it will increase its BOD and phosphorus loads by 90% and 82%, respectively, in relation to the current load. With the increase of WWTP discharge, there will be an expansion of hypoxic and anoxic conditions over the current areas, worsening the condition of this already jeopardized estuary. For the WWTP to lead to the expected environmental gains, it is necessary to consider the carrying capacity of the receiving body.